Зображуючи Трипілля: поява та занепад реалістичного стилю - Шатіло, Л.O.; Хофманн, Р. (Археологія і давня історія України, 2021)
У статті розглянуто різні категорії предметів
з реалістично зображеними елементами. На прикладі аналізу трипільської пластики, а також антропоморфних статуеток з середньо- та пізньонеолітичного телю Вінча, показано їхню часову та
просторову прив’язку до агломерованих регіонів у періоди з найвищою щільністю населення. This study, once again, raises the question on the driving
forces of stylistic development. For that, we focused
on two prehistoric contexts, more specifically on Trypillia
and the Late Neolithic site Vinča-Belo Brdo where we
analyzed various objects with «realistic» images.
For Trypillia, we included the following categories:
house models, sledge models, depictions of equipment
for animal use on zoomorphic objects (figurines, vessels
etc.), «realistic modelled» faces of anthropomorphic
figures, and depictions on anthropomorphic figurines
(hairstyles and accessories for hair, necklaces, footwear
and clothes). Based on the latest findings on chronology,
we trace the mentioned realistic features in time
and space by means of quantifications and mapping.
Additionally, we investigate the changes of anthropomorphic
figurines in terms of size.
In the case study of Vinča, the frequency of realistic
features in the different depths of the tell stratigraphy
are put in relation to the total number of figurines and
the historical dynamics of the late Neolithic societies.
The consideration of different material categories
shows that objects with «realistic» characteristics
mainly occur in certain periods and geographical regions
that are characterized by specific historical developments.
These include high population densities in
large agglomerated settlements, increased innovativeness,
intensive interaction in densified far-reaching
communication and exchange networks.
In both case studies, the developments ended in
fundamental crises and were associated with the disintegration
of large settlements and population decline.
Linked to this, some types of «realistic» objects disappear,
others become fewer and lose their «realistic»
characteristics.